Extended latissimus dorsi chimeric thoracoplasty with a vascular supercharge for Aspergillus empyema. (20th November 2019) - Shimomura, Masanori; Sowa, Yoshihiro; Yamochi, Ryo; Inoue, Masayoshi
Abstract: The latissimus dorsi and serratus anterior muscles are available for reconstruction coverage of thoracic defects. We performed extended latissimus dorsi-serratus anterior chimeric thoraco-myoplasty with a vascular supercharge to maintain sufficient blood supply to the flaps because of a deficiency in the distal blood flow to the flap revealed by an intravenous injection of indocyanine green and simultaneous endobronchial embolization for refractory Aspergillus empyema.